Observed and projected climatic changes, their impacts and adaptation options for Sri Lanka: a review - Eriyagama, Nishadi; Smakhtin, Vladimir U. (2010)
Climate is changing world-wide, and the science community in Sri Lanka has come up with ample evidence to suggest that the country?s climate has already changed. During 1961-1990 the country?s mean air temperature increased by 0.016 0C per year, and the mean annual rainfall decreased by 144 mm (7 %) compared to the period 1931-1960. In addition, mean annual daytime maximum and mean annual night-time minimum air temperatures increased. However, the bigger question of national importance is what Sri Lanka?s climate will look like in 50 or 100 years and how prepared is the country to face it. Apart from the Intergovernmental Panel on Climate Change (IPCC) projections at the coarse global scale, few studies have attempted to project future climate scenarios for Sri Lanka and to identify climate change impacts on agriculture, water resources, the sea level, the plantation sector, the economy and health. Vulnerability and adaptation to climate change are the least studied areas. This paper reviews the status of climate change research and activities in Sri Lanka with respect to future climate projections, impacts, climate change mitigation and the country?s ability to adapt, and identifies existing knowledge gaps. Messages emerging from this review suggest that Sri Lanka?s mean temperature during the North-East (December-February) and South-West (May-September) monsoon seasons will increase by about 2.9 0C and 2.5 0C, respectively, over the baseline (1961-1990), by the year 2100 with accompanying changes in the quantity and spatial distribution of rainfall. Extreme climate events are expected to increase in frequency. These changes will bring about widespread impacts on the country?s agriculture and economy For example, an increase of 0.5 0C in temperature can reduce rice yield by approximately 6%; extended dry spells and excessive cloudiness during the wet season can reduce coconut yield resulting in annual losses between $32 and $73 million to the economy. Pilot studies in the Galle District suggest that sea level rise could inundate about 20 % of the land area of Galle?s coastal District Secretariat Divisions. Adaptation measures already undertaken in the agriculture sector include the development of low water consuming rice varieties and the use of micro-irrigation technologies. Tools have been developed for predicting seasonal water availability within the Mahaweli Scheme and annual national coconut production. However, Sri Lanka is yet to undertake a comprehensive national study on the vulnerability of her water resources and agriculture to climate change. The formulation of detailed and reliable future climate scenarios for the country is therefore, urgently required.